USEFULNESS OF DIFFERENT HINTS IN SOLVING AN INSIGHT PROBLEM: RELATION-SHIP WITH METACOGNITIVE STRATEGIES - Martínez Fernández, Reinaldo; Tubaut, Elisabet; Guilera, Llorenç; Rabanaque, Samuel; Sánchez, Edgar (Anales de Psicología / Annals of Psychology, 2008)
In this work it is studied the relationship between metacogni-tion and the efficacy of different hints while solving an insight problem. Participants attempted to solve the three bulbs problem either without any hint or after receiving hints with different levels of abstraction, and an-swered the O’Neil & Abedi’s (1996) self-report inventory about metacog-nitive strategies. Surprisingly, the different hints did not improve perform-ance, compared to the no-hint condition. Nevertheless, a significant inter-action between type of hint and level in metacognition was revealed by additional analyses. Only a few participants (less than 30%) solved the problem when the hint was very abstract or no hint was presented, regard-less of their metacognitive level. However, the participants who scored higher on metacognition performed better when more direct hints, refer-ring to a key concept to solve the problem, were presented. Hence, these results suggest that metacognitive strategies play a significant role on recognizing the relevance of specific information to problem solving.